Modeling of Carbon Emissions and Sequestration Due to Land Cover Changes in Makassar Using Geospatial Technology - Nursaputra, Munajat; Fa'iq, Muhammad; Anila, Chaeria; Nasir, Anugrahandini; Larekeng, Siti Halimah; Rahmat, Syaeful (Tunas Geografi, 2024)
Land-use change significantly affects carbon emissions, particularly in rapidly growing cities such as Makassar. This study uses geospatial technology to analyze the impact of land cover changes on carbon emissions and sequestration in Makassar City from 2022 to 2041. The Rapid Carbon Stock Appraisal (RaCSA) method and the QUES-C feature of the LUMENS software were utilized to model land cover changes based on the Makassar City spatial planning scenario (RTRW). The results indicate that expanding residential areas and reducing green spaces, such as mangrove forests and agricultural land, have increased carbon emissions. However, carbon sequestration in certain areas, especially in the Tallo District and reclamation areas, has increased significantly due to the establishment of local protection zones. This study highlights the importance of spatial planning that supports the protection and restoration of green spaces to enhance carbon sequestration capacity and support sustainable development strategies in Makassar City.